2015
DOI: 10.1002/clen.201400711
|View full text |Cite
|
Sign up to set email alerts
|

Health Concerns Related to Consumption of Fish from Anzali Wetland

Abstract: Two hundred and forty fishes including Hypophthalmichthys molitrix, Silurus glanis, and Esox lucius (male and female) were collected from four sampling sites in Anzali wetland including Anzali, Khazarvila, Pirbazar, and Beshman through late April 2011. The potential health risk of Pb, Sn, and Zn to consumers was assessed by calculating the estimated daily intake, estimated weekly intake, hazard quotient, maximum allowable fish consumption rate, and monthly allowable consumption rate. In addition, the tissue st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…PCA revealed that different organs and tissues of fish have distinct capacities for the accumulation of HMs. It is probable that this is caused by differences in organ metabolic activity and function, as well as changes in environmental contamination [87,88]. Metal concentrations in tissues of different fish species may be related to metabolic peculiarities, age and size of the fish, as well as their habitat and food source [89,90].…”
Section: Heavy Metal Content In Fish Tissuesmentioning
confidence: 99%
“…PCA revealed that different organs and tissues of fish have distinct capacities for the accumulation of HMs. It is probable that this is caused by differences in organ metabolic activity and function, as well as changes in environmental contamination [87,88]. Metal concentrations in tissues of different fish species may be related to metabolic peculiarities, age and size of the fish, as well as their habitat and food source [89,90].…”
Section: Heavy Metal Content In Fish Tissuesmentioning
confidence: 99%
“…Fish accumulate metals through respiration, adsorption, and ingestion. Different tissues have different accumulating capacities of metals, which may be due to differences in metabolic activity, changes in environmental pollution and functions of organs [143,144]. Furthermore, metal levels in different fish species might be due to different ecological requirements, metabolisms, age, size, and length of the fish, their habitats and feeding patterns [9,145].…”
Section: Comparison Of Metal Levels In Fish Tissuesmentioning
confidence: 99%